A Natural Food Fight: The Battle Between the “Natural” Label and GMOs - Colleen Gray (Washington University Journal of Law & Policy, 2016)
This note addresses the complex nature of food labeling in the United States, specifically in relation to the rise of “natural” products. Gray analyzes the history of food labeling, focusing on the use of the term “natural” in relation to products containing genetically modified organisms (GMOs). Gray then argues that due to a lack of regulation by the FDA on what the term “natural” means, consumers have a right to know that the “natural” product they are consuming may contain GMOs.
Keywords: GMO; Natural products; Natural food; FDA; Regulation; Genetically modified organisms; Labeling; FFDCA; NLEA